Engineering Yarrowia lipolytica for the production of β-carotene by carbon and redox rebalancing - Hojun Lee; Jinwoo Song; Sang Woo Seo (Journal of Biological Engineering)
Abstract Background β-Carotene is a natural product that has garnered significant commercial interest. Considerable efforts have been made to meet such demand through the metabolic engineering of microorganisms, yet there is still potential for improvement. In this study, engineering approaches including carbon and redox rebalancing were used to maximize β-carotene production in Yarrowia lipolytica. Results The initial production level was increased by iterative overexpression of pathway genes with lycopene inhibition removal. For further improvement, two approaches that redirect the central carbon pathway were evaluated to increase NADPH regeneration and reduce ATP expenditure. Pushing flux through the pentose phosphate pathway and introducing NADP+-dependent glyceraldehyde-3-phosphate dehydrogenase were found to be more effective than the phosphoketolase-phosphotransacetylase (PK-PTA) pathway. Furthermore, flux to the lipid biosynthesis pathway was moderately increased to better accommodate the increased β-carotene pool, resulting in the production level of 809.2 mg/L. Conclusions The Y. lipolytica-based β-carotene production chassis was successfully developed through iterative overexpression of multiple pathways, central carbon pathway engineering and lipid pathway flux adjustment. The approach presented here provides insights into future endeavors to improve microbial terpenoid production capability.